Digital customer service: overcoming the effects of customer resistance in shipping logistics - Yeo, Ezra En Zhu (Nanyang Technological University, 2022)
Digitalisation, supply chain ecosystem and customer service have become increasingly popular buzzwords in today’s globalised world and increasingly integrated supply chains. Within the shipping logistics industry, attempts to introduce and integrate various transformational digital technologies have increased in the last few years, although the actual rate of digital transformation has been much slower than expected. An accurate conceptualisation of why digitalisation (henceforth digitisation) initiatives fail should involve an understanding of the socio-cultural barriers to adoption and manifestations of psychological resistance to change. This paper aims to identify and define the concept of ‘customer resistance’ (CR) as a primary cause of failed initiatives and examine the real-life applicability of this idea within the scope of the shipping logistics supply chain. Based on the findings, a set of potential solutions is proposed to overcome the phenomenon of CR.